Current Issues of Legal Culture Formation - AKHMETOV, Arman Serikovich; ZHAMULDINOV, Victor Nikolaevich; KOMAROV, Oleg Evgenievich (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The purpose of this article is to present a comprehensive analysis and study of existing scientific approaches to the formation of legal culture in the context of the formation of a democratic state, as well as to develop specific recommendations and ways to improve the level of the legal culture of society. The methodological basis of this work is formed by a set of general scientific and special legal methods of cognition. All the scientific approaches to the current issues of legal culture studied in the work made it possible to develop an author’s justified position based on the existing achievements of legal scholars in the nature and essence of legal culture and its features. Based on domestic and foreign sources, the research allowed us to analyze the existing approaches to the study of the phenomenon of legal culture, to elaborate basic provisions that can serve as a basis for the development of the level of the legal culture of society, as well as to develop a number of measures, which will help to increase the quality of legal education and effectively combat corruption manifestations in society. The study of the current issues of legal culture formation involves almost all areas of state activities and affects the success of ongoing legal reforms in the country.